1998
DOI: 10.1006/jabr.1997.7361
|View full text |Cite
|
Sign up to set email alerts
|

Fat Points, Inverse Systems, and Piecewise Polynomial Functions

Abstract: ŽWe explore the connection between ideals of fat points which correspond to n Ž . . subschemes of ‫ސ‬ obtained by intersecting mixed powers of ideals of points , and Ž . piecewise polynomial functions splines on a d-dimensional simplicial complex ⌬ d w x embedded in R . Using the inverse system approach introduced by Macaulay 11 , we give a complete characterization of the free resolutions possible for ideals in w x Ž k x, y generated by powers of homogeneous linear forms we allow the powers to . differ . We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 10 publications
1
69
0
Order By: Relevance
“…by equation (3) and h 0 (S(I)(m)) = h 1 (D m ) = 0 by equation (9). Now, by equation (10), we have an exact sequence Lemma 4.6.…”
Section: Proposition 32 Given General Linear Formsmentioning
confidence: 89%
See 3 more Smart Citations
“…by equation (3) and h 0 (S(I)(m)) = h 1 (D m ) = 0 by equation (9). Now, by equation (10), we have an exact sequence Lemma 4.6.…”
Section: Proposition 32 Given General Linear Formsmentioning
confidence: 89%
“…Whenever h 0 (S(I)(t + 1)) < h 0 (S(I )(t + 1)), we thus see that μ fails to be injective. This is precisely what occurs if (r, t, n) ∈ {(4, 3, 5), (5,3,9), (6,3,14), (6, 2, 7)}. For example, let (r, t, n) = (4, 3, 5) and consider the divi-…”
Section: Proposition 32 Given General Linear Formsmentioning
confidence: 98%
See 2 more Smart Citations
“…In [Lundqvist et al (2017), Lemma 2.2], it was also shown that Conjecture 2.4 holds in the case of binary forms. The proof is obtained by specializing each one of the g i 's to be the d-th power of a generic linear form and applying the fact that generic power ideals in two variables have the generic Hilbert series Geramita and Schenck (1998). It is worth to mention that the same idea as in [Lundqvist et al (2017), Lemma 2.2] gives a positive answer to Problem F in the case of binary forms, by specializing i,1 = .…”
Section: Conjecture 24 (Nicklasson (2017a))mentioning
confidence: 99%